High resolution study on planktonic foraminifera across the Paleocene-Eocene thermal maximum in the expanded Tethyan Forada section ( Italy): paleoecological and paleoenvironmental implication - LUCIANI V; BACKMAN J; AGNINI, CLAUDIA; FORNACIARI, ELIANA; GIUSBERTI, LUCA; RIO, DOMENICO (2007)
Geophysical Research Abstracts